Dialogue in poetry Andalusian encyclopedias, selected samples - Resea. Dhifaf Ali Hameed; Dr Rasoul Deglazed; Dr Mahdi Naser (Journal of College of Education, 2024)
Dialogue is generally presented as a process of consultation to seek to achieve common understanding .The gateway effective listening . Dialogue is an important pillar of the continuous work of poetry and one of elements of storytelling for dramatic construction. As for the concept of dialogue, it is included in the critical study that deals with it ,and its developments and sections are numerous. Dialogue is defined as stated in Arabic . Dictionary and terminology as a conversation that takes place between two or more personal in joint Narrative or artistic work . this study seeks to shed Light on the reglected element . Andaluian encyclopedias: These are Books and writing that are concerned with the history of the country of Andalusia and its poets in the prosperity and renaissance of Andalusia. From the time of Islamic Conquest until its fall. These encyclopedias are distinguished by their rich. Knowledge in all its intellectual and literary fields until scholars interested in this appeared : The message produced results Dialogues is one of important elements of the dramatic structure in poetry and prose represent by the story and narrative of the play it is not concerned with one aspect but rather we find it on many topic